EVALUASI KEBIJAKAN PERATURAH DAERAH JEPARA NOMOR 2 TAHUN 2014 TENTANG PERLINDUNGAN, PEMBERDAYAAN DAN PEMBINAAN INDUSTRI MEBEL DI KABUPATEN JEPARA - Nahdya Yuris Adila; Teguh Yuwono (Journal of Politic and Government Studies, 2020)
Furniture industry in Jepara is the backbone of the economy, so it needs a policy to improve its existence and productivity. This research aims to determine the evaluation of the regional Policy assessment Jepara Number 2 year 2014 about the protection, empowerment and development of furniture industry and the factors that inhibit the development of furniture industry which is influential in the implementation of the policy.The research methodology used is mixed method with data collection techniques such as interviews, data/archives, and questionnaires. Then analyzed using triangulation theory, source and method. The results showed that the policy was not optimal. This policy has been effectively through the service of coaching, empowerment and protection but not efficient because of the lack of budgets and the implementation of socialization and the absence of SOP.Its policy results have been able to improve the furniture industry that is competitive and independent so that it can improve the export of furniture industry. In addition there are facilitation of training activities, exhibitions, people's Business credit (KUR), road infrastructure, bridges, raw materials and furniture centers in Jepara, thus giving a good impact in the form of increased effort for the culprit. There are objectives that have not been achieved due to the factors that inhibit the scarcity of raw materials, limitations of quality and quantity of labor, disrupted market share conditions, online marketing abuse and the existence of The policy PMA and timber Log and SVLK which complicates the perpetration.Researchers recommend to improve the implementation of the policy for maximum.Keywords: Evaluation, Barriers To Furniture Industry, Coaching, Empowerment, Protection